Analisis Pendapatan Usaha Pengolahan Sagu (metroxylon sp.) di Kelurahan Andabia Kecamatan Anggaberi Kabupaten Konawe - Mursal Junus (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to determine the income and feasibility of sago processing business in Andabia Village, Anggaberi District, Konawe Regency. The research was carried out in March 2025 using the purposive sampling method, based on the consideration that the sago processing business has long been the main livelihood of the local community. The sample was taken by census of 13 respondents. Data analysis using revenue model I = TR - TC and business feasibility analysis with an R/C = TR / TC ratio approach. The results of the study show that in one sago processing process, the total revenue reaches IDR 18,000,000, while the total cost is IDR 7,863,269. Thus, the net income obtained by sago processors is IDR 10,136,731. The business feasibility analysis shows an R/C ratio value of 2.29, which means that every expenditure of IDR 1 generates IDR 2.29 in revenue. The R/C value > 1 indicates that the sago processing business in the region is profitable and feasible to be developed. These findings provide a basis for strengthening the local economy through optimizing the sago business as a sustainable source of income. This study also recommends policy support and technical training to improve the efficiency and competitiveness of sago processing businesses in the area.